UPAYA MENINGKATKAN KOMPETENSI GURU DALAM MENGELOLA ADMINISTRASI KELAS MELALUI SUPERVISI KLINIS PADA GURU DI SD NEGERI SENDANG 01 TAHUN PELAJARAN 2018/2019 - Sukemi Sukemi (Universitas Ngudi Waluyo, 2020)
The School Action Research conducted aims to determine the ability of teachers to manage classroom administration in Sendang 01 Public Elementary School in Bringin District in the 2018/2019 academic year in planning, implementing the learning process, and administrative completeness faced by teachers through clinical supervision. The study was conducted in two cycles with 9 subjects. Data collection is done by observing the data for the teacher's ability to plan the learning process and completeness of the administration of learning. Furthermore, the data was analyzed by using statistics descriptive method. The results show that the implementation of clinical supervision can improve the ability of teachers to manage the learning process.